Estimation of Naratriptan Hydrochloride in Bulk and Formulation by First Order Derivative UV-Spectrophotometric Methods - Jayshri S. Borse, Atul A. Shirkhedkar (Journal of Applied Pharmaceutical Science)
Naratriptan Hydrochloride is a triptan drug used for the treatment of migraine headaches and is a selec¬tive 5-hydroxytryptamine 1 receptor subtype agonist. Two simple, precise and economical UV-Spectrophotometric methods have been developed for the determination of Naratriptan Hydrochloride in pharmaceutical dosage form. In Method I, zero order spectrum of Naratriptan Hydrochloride was derivatized into first order (Δ λ = 2, scaling factor = 9) using UV-probe software and the amplitude of the trough was recorded at 232.2 nm. While in ‘Method II’, area under curve (AUC) of the first order derivative spectrum was selected between 294.20 – 299.00 nm. In Method I and II, Naratriptan Hydrochloride obeyed linearity in the concentration range of 10 - 60 µg/ml. The coefficient correlation (r2) in Method I and II were found to be r2 = 0.999 and r2= 0.998, respectively. The % amounts of Naratriptan Hydrochloride quantified by Method I and Method II was found to be 98.79 % and 99.43%. The developed methods were validated statistically and by recovery studies.
Keywords: Naratriptan Hydrochloride, First Order Derivative, Area under Curve technique.